La paradoja de la ley - Rentería Hinestroza, Karla Yineth (Universidad de San Buenaventura - Cali, 2018)
This article comes to present a way to reflection going through some clinical bullets about the enforcement of law and also the paradox of itself in a particular man , whom is representing it acting as a cop in the city of Buenaventura; to reach this goal we present two different kind of aproachment to the concept that even being oposite runs together in this scenario, one is the law and jurisprudence and the other is the concept of law in psychoanalysis based on Sigmund Freud postulations. The result of the theorical revisions and my own clinical experience working in the case presented here, shows that even being the same concept, the specificity of psychoanalysis shows the subjectivization among the individual and invite us to the knowledge of his function, going through his own psychic training; the case of this cop called L, whom has being choosen by the questions coming to me on our clinical sesions, allows me to conclude that even when “L” doesnt relate in a healthy way with society uses the investment as law officer to create an agresive hostil bridge with it. Being a cop doesnt build the person carrying the uniform, to represent the law doesnt destroy his strongest pulsions making him an offender. Being a cop doesnt mean he is not a subject